Community Empowerment Through Organic Fertilizer Processing of Tofu Liquid Waste in Ledok Kulon Bojonegoro - muafidah, Lailia; Saputri, Wahyu; Aisy, Rehadatul (Lembaga Dongan Dosen, 2023)
In the tofu production process, there is liquid waste derived from washing soybeans, boiling and filtering from tofu pressing. This fluid contains high levels of protein and can be decomposed immediately. So many tofu producers in Ledok Kulon cause several positive and negative impacts. The negative impact is the occurrence of waste pollution from tofu producers, where the waste pollutes the environment and even worse the processing is disposed of in Bengawan Solo. The purpose of this community service is to carry out assistance in processing tofu liquid waste into liquid organic fertilizer (POC). The materials used are tofu liquid waste, coconut water, EM4, molasses, bran, lemongrass leaves, and shrimp paste. All ingredients are mixed and fermented for 14 days, after which they can be applied to the soil by Ibu PKK which helps the process of improving soil structure. Evaluation on the implementation is carried out in order to monitor the fermentation process and make good use of fertilizer